“Descended from Immigrants and Revolutionists”: How Family History Shapes Immigration Policy Making - Feigenbaum, James; Palmer, Maxwell; Schneer, Benjamin (Quarterly Journal of Economics, 2025)
Abstract Does family history matter for policy making in democracies? Linking members of Congress (MCs) to the census, we observe countries of birth for members, their parents, and their grandparents, allowing us to measure ancestry for the politicians in office when U.S. immigration policy changed dramatically, from closing the border in the 1920s to reshaping admittance criteria in the 1960s. We find that legislators descended from immigrant parents or grandparents support more permissive immigration legislation. They are also less likely to speak negatively about immigration in speeches before Congress. A regression discontinuity design analyzing close elections, which addresses district-level selection and holds district composition constant, confirms our results on roll call voting and speech. Efforts to account for selection into immigration—such as comparing international immigrants to domestic migrants and exploiting variation in restrictive legislation targeting specific regions of origin—further confirm the relationship between family immigration experience and more permissive stances on immigration policy. We then explore mechanisms, finding support for in-group identity in connecting family history with policy making. MCs name their children in ways that express immigrant identity, and immigrant-descended MCs discuss immigration using more personal frames, emphasizing family over economic considerations. Our findings illustrate the important role of personal background in legislative behavior in democratic societies, even on major and controversial topics like immigration, and suggest how experiences transmitted from previous generations can inform lawmakers’ views.